Model of Spiritual Culture of Madurese People in Resilience and Adaptation of New Normal - Faisal Amir; Rahmad Wahyudi; Sitti Sulaihah (Faculty of Nursing Universitas Padjadjaran, 2022)
Background: From the beginning of its initial appearance until mid-2021, Corona Virus Disease-19 (Covid-19) is a feared outbreak around the world, including in Indonesia and particularly in Madura. The negative perception of stress will further weaken self-strength both physically and mentally so that resilience and coping mechanisms tend to be maladaptive. Purpose: This study aimed to analyze the spiritual culture of Madurese communities in resilience and physical health. Methods: This analysis will later become the basis in the formulation of a model of spiritual cultural towards resilience, and physical health. In the design of explanatory observational research, the first stage is to explain the construct and its contributing indicators. The second stage is to conduct FGD with respondents as well as to consult with experts. The population is a community on the island of Madura with a sample consisting of 400 respondents using probability sampling, namely cluster random sampling based on a predetermined population area. The exogenous variable is the culture of spirituality. Endogenous variables are resilience and physical health. Data were collected using questionnaire research and analyzed using structural models with SmartPLS (Partial Least Square) software. Results: The results showed that spirituality culture factors had a positive effect on resilience with a coefficient of 0.449. Spirituality culture factors had a positive effect on physical health with a coefficient of 0.161, and resilience factors had a positive effect on physical health with a coefficient of 0.172. Conclusion: This indicates that the higher the spiritual culture of the Madurese community, the higher the resilience, psychological well-being, and physical health, especially during the COVID-19 pandemic.